Somalia and the Islamist War: Assessing the Probability of Al-Shabab Winning or Losing the War with Somalia - issa salwe, abdisalam (Advances in Social Sciences Research Journal, 2022)
In this article, we assess the ongoing conflict between al-Shabaab on the one hand, and the Somali Transitional Federal Government (TFG) and the African Union Mission in Somalia(AMISOM), on the other. Though al-Shabab has been around since the mid 2000s, the current round of the conflict began in 2010 when AMISOM was deployed to Somalia to bolster the fledgling Somali government. The main thrust of the paper, therefore, is to reexamine what effect, if any, this African force has had on the conflict. Data were collected from 2009-2021 through monitoring and analysis was done using software. Data gathered included recording specific instances of violence between the two groups, including who orchestrated the violence, the location of the violence and the fatalities in each act of violence. While TFG/AMISOM made substantial gains initially against al-Shabab, the result did not specifically conclude which of the two groups is poised to win the war. However, it demonstrates that al-Shabab is able to stay in play by resorting to a host of other strategies which neither the TFG nor AMISOM can deploy.